Screening foreign direct investment in the EU political rationale, legal limitations, legislative options - Velten, Jens 1990- (EYIEL Monographs - Studies in European and International Economic Law, 2022)
Introduction -- Part I Setting out the background of FDI Screening in the EU -- Part II FDI screening mechanisms on the grounds of 'security or public order' and 'public policy or public security" -- Part III Flexibility for FDI screening on broader grounds than 'security or public order" -- Conclusion.